Feed Evaluation Based on in Vitro Gas Production of Tropical Forages with Addition of Different Polyethylene Glycol (Peg) Level - Widya Kenshiana Putri; Cuk Tri Noviandi; Kustantinah Adiwimarta (Faculty of Animal Science, Universitas Gadjah Mada, 2021)
This study aimed to determine the chemical composition and gas production based on fermentation in the rumen of nine types of forage tropical feed commonly used in Indonesia. The forages used in this study were: mahogany leaves (Swietenia mahagoni L. Jacq.), tayuman leaves (Bauhinia purpurea), bamboo leaves (Bambusa arundinaceae), canary leaves (Canarium indicum L.), tea leaves (Camellia sinensis), ketapang leaves (Terminalia catapa L.), lamtoro leaves (Leucaena leucocephala), tehtehan leaves (Duranta repens), and turi leaves (Sesbania grandiflora). Measurements of in vitro gas production were carried out at 10 observation points (2, 4, 6, 8, 12, 16, 24, 36, 48, 72 hour). Tannin activity was measured for each sample at observation points using measurements of gas production divided into three groups with modified levels of polyethylene glycol (PEG), ie samples without PEG (P1); sample + PEG in the amount of 200 mgDM (P2); and PEG + samples of tannins contained in each forage based on literature studies (P3). Data were analyzed for a variance by following the factorial completely randomized design (CRD) pattern. Statistical analyzes were performed on all data by following the general linear procedure in PROC GLM from SAS. The data obtained were analyzed for variance at the 5% significance level. The results of gas production calculations showed that crude protein (CP) from each forage ranges from 5.75 - 22.37% where the highest CP was owned by turi leaves (S. grandiflora). The content of crude fiber (CF) ranged from 5.30 - 20.93%. The most optimal measurement of gas production was in the sample given PEG in the amount of 200mg/kg with a significant difference (P<0.05). The higher of the tannin content contained in the forage, the lower of gas produced. Measurement of tannin content showed that condensed tannin content varied from turi leaves by 0.20% to the highest in mahogany leaves by 8.60%. The addition of 200 mg/100mgDM of PEG optimizes the rate of forage gas production, especially for grass plants (gramineae).